Elaboration of wild blackberry (Rubus fructicosus L.) nectar - Valencia, Cristina (2013)
In this research work was developed and characterized physicochemically blackberry nectar. Operations included in this process were: sorting, grading, washing, disinfection (sodium hypochlorite 100 ppm Free Chlorine Residual), pulping, refined, standardized, homogenization, pasteurization and packaging. In the raw material was found: 82.98% moisture, 0.93% protein, 15.74% carbohydrate, no fat, 2.48% fiber, 0.42% ash, 3.91% reducing sugar, 0.93% acidity, 3.4 pH, 10.5 °Brix, 400.67 mg of gallic acid/100 g sample of total phenolic compounds, 39.02 μmol Trolox / g of antioxidant capacity, 109.07 mg cyanidin 3-glucoside / 100 g sample of anthocyanin and 14.37 mg / 100 g of vitamin C. The fruits reported a yield of 78.2% pulp. Trials were conducted preliminary processing blackberry nectar at different dilutions (1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 and 1:3), degrees °Brix (11,12 and 13) and pH values (3.4, 3.6 and 3.8). Given the greater acceptance in the sensory evaluation (extended preference test with 30 untrained judges whose results were statistically evaluated by nonparametric Friedman), was elected to the dilution containing 1:2.7 (pulp:water), 12 °Brix, 0.07% CMC and 3.8 pH. Nectar obtained reported: absence of fat and fiber, 87.3% moisture, 0.10% protein, 0.10% ash, 4.87% reducing sugars, 0.23% acidity, 3.8 pH, 115.25 mg gallic acid / 100 g sample of total phenolic compounds, 3.9 μmol Trolox / g of antioxidant capacity, 24.33 mg cyanidin 3-glucoside / 100 g sample of anthocyanins and 3.9 mg / 100 g of vitamin C.